2013
DOI: 10.1371/journal.pone.0063691
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Baseline Brain Activity in Non-Depressed Parkinson’s Disease and Depressed Parkinson’s Disease: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: Depression is the most common psychiatric disorder observed in Parkinson’s disease (PD) patients, however the neural contribution to the high rate of depression in the PD group is still unclear. In this study, we used resting-state functional magnetic resonance imaging (fMRI) to investigate the underlying neural mechanisms of depression in PD patients. Twenty-one healthy individuals and thirty-three patients with idiopathic PD, seventeen of whom were diagnosed with major depressive disorder, were recruited. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
88
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 61 publications
10
88
1
Order By: Relevance
“…The altered ALFF in the right DLPFC therefore suggests that there is cognitive impairment in subjects with nCDSs. Similar to previous findings in subclinical samples (Felder et al, 2012) and depressed patients with Parkinson's disease (Wen et al, 2013), the depressive severity scores of subjects with nCDSs were related to the ALFF values of the right DLPFC in the present study. This suggests that the right DLPFC is the crucial brain region that mediates depressive emotion in individuals with nCDSs.…”
Section: Discussionsupporting
confidence: 91%
“…The altered ALFF in the right DLPFC therefore suggests that there is cognitive impairment in subjects with nCDSs. Similar to previous findings in subclinical samples (Felder et al, 2012) and depressed patients with Parkinson's disease (Wen et al, 2013), the depressive severity scores of subjects with nCDSs were related to the ALFF values of the right DLPFC in the present study. This suggests that the right DLPFC is the crucial brain region that mediates depressive emotion in individuals with nCDSs.…”
Section: Discussionsupporting
confidence: 91%
“…Of the 38 studies on depression, 33 reported findings from one single imaging modality: 19 used either PET [11, 12, 13,15, 16, 17, 18, 19] or SPECT 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 techniques, four used T1‐weighted imaging 31, 32, 33, three used DTI 34, 35, 36, six used resting state functional MRI (RS‐FMRI) 37, 38, 39, 40, 41, 42 and two used TCS methods 43, 44. The remaining four of the 38 studies reported findings from structural T1‐weighted imaging plus another imaging method, including PET 14, DTI 45, task FMRI 46 and RS‐FMRI 47, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Vriend et al (2014a) reviewed neuroimaging studies of depression in PD and highlighted decreased dopaminergic function in the ventral striatum. MRI studies of co-morbid depression in PD have also shown alterations in ALFF and morphometric result although they are notable for some inconsistent results in ALFF results (Luo et al, 2014a; Skidmore et al, 2013b; Wen et al, 2013) and morphometric studies (Surdhar et al, 2012; van Mierlo et al, 2015). …”
Section: Neuroimaging Of Pdmentioning
confidence: 99%